Curricular Congruence at an Implementation Level Are Two Interventions of a District's Early Literacy Project (Improved Classroom Instruction and Reading Recovery) Working Congruently To Address the Needs of Low-Achieving Readers? / J. Wilson-Bridgman. - Wilson-Bridgman, J. (Distributed by ERIC Clearinghouse, 2003)
Historically when children have experienced difficulty in learning to read they have been served by remedial reading programs, special education programs, or retention practices. There is considerable evidence that these programs have been ineffective in raising the achievement levels of those they serve. In addition, because these programs are generally provided as a means of supplementing rather than supplanting the regular classroom program, the ineffective programming is confounded by a lack of articulation and lack of congruency between the two programs. This case study research examines the implementation of a district's Early Literacy Project whose goal was to establish curricular congruence for struggling readers who receive instruction both in their regular classroom and in a remedial setting. More specifically, it examines whether two interventions (improved classroom instruction and Reading Recovery) are working congruently along five curricular components: philosophy; instructional materials; instructional methods and student activities; reading strategies; and reading goals. In one case study, congruence between reading programs helped to alleviate tension the student felt toward reading, while in the second case study the student began to receive more appropriate instruction. (Contains 19 references.) (Author/RS)
ERIC Document Number: ED478118.
Keywords: Case Studies.; Curriculum Development.; Educational Objectives.; Instructional Effectiveness.; Literacy.; Primary Education.; Program Implementation.; Reading Instruction.; Reading Strategies.; Remedial Instruction.; Student Attitudes.